2000
DOI: 10.1164/ajrccm.161.5.9908028
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Expression and Release in Allergic Inflammatory Disease of the Upper Airways

Abstract: It is well known that allergic airways disease is characterized by inflammation and hyperresponsiveness, but the link between these two conditions has not been elucidated. We have previously shown that in allergic rhinitis, hyperresponsiveness is attributable to increased neural reactivity. We thus hypothesized that nerve growth factor (NGF), which is expressed by inflammatory cells and effects changes that lead to increased neural responsiveness, could be a pivotal mediator in this disease. Using reverse tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(107 citation statements)
references
References 43 publications
6
99
0
1
Order By: Relevance
“…These findings suggest that activation of neurotrophins may be an alternative pathway in AR pathogenesis. In our study, we found that NT-3 staining levels of nasal mucosa were higher in the AR group than in the control group; this finding is similar to the literature regarding other neurotrophins (2,16,22) Increases in serum neurotrophin levels in allergic diseases has also been shown (12,16), whereas, in the study of Raap et al (16), this increase was not statistically significant both before and after nasal provocation tests. Furthermore, it is also known that neurotrophins have autocrine or paracrine features.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings suggest that activation of neurotrophins may be an alternative pathway in AR pathogenesis. In our study, we found that NT-3 staining levels of nasal mucosa were higher in the AR group than in the control group; this finding is similar to the literature regarding other neurotrophins (2,16,22) Increases in serum neurotrophin levels in allergic diseases has also been shown (12,16), whereas, in the study of Raap et al (16), this increase was not statistically significant both before and after nasal provocation tests. Furthermore, it is also known that neurotrophins have autocrine or paracrine features.…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that NGF levels of nasal lavage fluid were higher (22) and NGF and BDNF were overexpressed in nasal tissue of AR patients (16). Raap et al (23) showed that eosinophil apoptosis is inhibited when eosinophils are stimulated by NT-3.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms of hyperresponsiveness are not understood, but several inflammatory products appear to play a role. Neurotrophins, such as the nerve growth factor (122), are prime candidates for mediators of neural hyperresponsiveness.…”
Section: Mechanisms: Neurogenic Mechanismsmentioning
confidence: 99%
“…Among the family of neurotrophins most attention has been given to NGF as a potential mediator in afferent plasticity in inflamed airways. NGF is found in human airways, and the NGF content of airway lavage fluid is increased following allergen challenge (61,(64)(65)(66). NGF is capable of regulating the expression of mRNAs encoding the precursors of substance P and CGRP in mature afferent neurons (67).…”
Section: Induction Of Tachykinin Synthesis In Afferent Neuronsmentioning
confidence: 99%